PENGAYAAN KOSA KATA BAHASA INGGRIS MELALUI MULTIMEDIA VIDIO DI PESANTREN BISMAR AL-MUSTAQIN SURABAYA - Cahyanigsih Pujimahanani; Putut Handoko; Kusuma Wijaya; Ahmad Choiron; Windi Setiawan (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
This Community Partnership Program deals with community service activity on English Vocabulary Training for students at  Bismar Al-Mustaqin Islamic Boarding school held in August-October 202*2. The partner's problem is Santri orphans have not received English Language Training through digital media  learning. The solution given is training using  digital media The material of training covers singing a song about fruits and animals, Game on animals. At Evaluation step, students are given a test of mastering vocabulary/: fruits and animals with a very good result.